Quantitative analysis of synaptic contacts made between functionally identified oralis neurons and trigeminal motoneurons in cats - Yoshida, A.; Fukami, H.; Nagase, Y.; Appenteng, K.; Honma, S.; Zhang, L.; Bae, Y.C.; Shigenaga, Y. (Journal of Neuroscience, 2001)
A previous study revealed that rostrodorsomedial oralis (Vo.r) neurons synapsing on trigeminal motoneurons use GABA and/or glycine as neurotransmitters. To determine the number and spatial distribution of contacts, injections of biotinamide and horseradish peroxidase were made into a Vo.r neuron and an α-motoneuron in the jaw-closing (JC) and jaw-opening (JO) motor nucleus, respectively, in 39 cats. All Vo.r neurons responded to low-threshold mechanical stimulation of the oral tissues. Single Vo.r neurons terminating in the JC nucleus (Vo.r-dl neurons; n = 5) issued, on average, 10 times more boutons than Vo.r neurons terminating in the JO nucleus (Vo.r-vm neurons; n = 5; 4437 vs 445). The Vo.r-dl neuron-JC α-motoneuron pairs (n = 4) made contacts on either the somadendritic compartment or dendrites, and the Vo.r-vm neuron-JO motoneuron pairs (n = 2) made contacts on dendrites, with a range of two to seven contacts. In five of the six pairs, individual or groups of two to three terminals contacted different dendritic branches of a postsynaptic cell. The Vo.r-dl neurons innervated a greater number of counter-stained motoneuronal somata than did the Vo.r-vm neurons (216 vs 26). Total number of contacts per Vo.r neuron was higher for the Vo.r-dl than Vo.r-vm neurons (786 vs 72). The present study demonstrates that axonal branches of Vo.r neurons are divided into two types with different innervation domains on the postsynaptic neuron and that they are highly divergent. The overall effect exerted by these neurons is predicted to be much greater within the JC than JO motoneuron pool.
Keywords: Contact; Horseradish peroxidase; Motoneuron; Neurobiotin; Sensorineuron; Trigeminal